2010
DOI: 10.1016/j.physleta.2010.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement preservation of two coupled modes

Abstract: The dynamics of two coupled modes sharing one excitation is considered. A scheme to inhibit the evolution of any initial state in subspace {|1 a , 0 b , |0 a , 1 b } is presented. The scheme is based on the unitary interactions with an auxiliary subsystem, and it can be used to preserve the initial entanglement of the system.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…We can control the system by interrupting the free evolution periodically with a certain operation, so that the state of the controlled evolution is confined in a subset of a state space very close to the initial state and the entanglement can be preserved very well. This idea is inspired by prior work of R. Rossi [22].…”
Section: Model and Schemementioning
confidence: 99%
“…We can control the system by interrupting the free evolution periodically with a certain operation, so that the state of the controlled evolution is confined in a subset of a state space very close to the initial state and the entanglement can be preserved very well. This idea is inspired by prior work of R. Rossi [22].…”
Section: Model and Schemementioning
confidence: 99%
“…Therefore, researchers used several strategies to preserve entanglement for a long time limit to allow the performances of quantum computation and quantum communication. In this regard, it was shown that the evolution of a quantum system can be slowed down or even frozen by frequent repeated projective measurements during a defined period of time which is known as the quantum Zeno effect [2,3,4,5]. Also, the other way for protecting the entanglement was performed by modulating the detuning between the qubits and the central frequency of an imperfect cavity [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is very important to find out a mechanism whose advantage leads to an effective long-time entanglement preservation. So far, a lot of researches have been devoted to entanglement manipulation and protection, such as quantum Zeno effect (QZE) [4,5,6,7] and detuning modulation [8,9].…”
Section: Introductionmentioning
confidence: 99%